2018
DOI: 10.1016/j.radonc.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an MRI-based model to predict response to chemoradiotherapy for rectal cancer

Abstract: An MRI-based prediction model of (near-)complete pathological response following CRT in rectal cancer patients, shows a high predictive performance in an external validation cohort. The clinically relevant features in the model make it an interesting tool for implementation of organ-preserving strategies in rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Radiomics is an emerging field concerned with the high-throughput extraction of innumerable quantitative imaging features, complementing and accelerating the advancement to mine the medical images [23,24]. Radiomic features are showing great potential for predicting diagnosis [[25], [26], [27]], survival, treatment response [[28], [29], [30], [31], [32], [33], [34]], and molecular properties of tumors [24,30,32,35].…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is an emerging field concerned with the high-throughput extraction of innumerable quantitative imaging features, complementing and accelerating the advancement to mine the medical images [23,24]. Radiomic features are showing great potential for predicting diagnosis [[25], [26], [27]], survival, treatment response [[28], [29], [30], [31], [32], [33], [34]], and molecular properties of tumors [24,30,32,35].…”
Section: Introductionmentioning
confidence: 99%
“…In striking contrast, however, it is well known from radiotherapy that most malignancies do not resolve during multi-week fractionated radiation treatment. Indeed, most malignancies require several weeks after the end of treatment to show volumetric tumor regression in clinical and imaging assessment [ 2 , 3 ]. In rectal cancer for example, Habr-Gama et al found a median time interval of 18.7 weeks from completion of radiotherapy to complete endoscopic clinical response [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have reported the application of diffusion-weighted imaging (DWI) parameters and dynamic contrast-enhanced MRI in the prediction of patho-logic response after NCRT for rectal cancer [24][25][26]. In particular, Bulens et al [24] built a model with T2-volumetric and DWI parameters and showed its good predictive performance for good pTRG (area under the curve, 0.89; 95% confidential interval, 0.79 to 0.98). The combination of 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) parameters is also considerable.…”
Section: Discussionmentioning
confidence: 99%